Pengaruh Doping Ag pada Sintesis Nanopartikel CuO dan Aktivitas Fotokatalitik untuk Degradasi Rhodamin B - Aysha Famil Hidayah; Hary Sanjaya; Desy Kurniawati; Deski Beri (Lembaga Yasin AlSys, 2026)
Textile dye wastewater contamination, particularly by Rhodamine B, is a serious environmental problem because it is toxic and difficult to degrade naturally. This study aimed to synthesize and evaluate the photocatalytic performance of pure CuO nanoparticles and Ag-doped CuO for the degradation of Rhodamine B. The materials were synthesized using the sol–gel method with an Ag doping concentration of 0.2 mmol. The optical properties were characterized using UV–Diffuse Reflectance Spectroscopy (UV-DRS) in the wavelength range of 185–1100 nm to determine the bandgap energy values using the Kubelka–Munk equation. Photocatalytic activity was tested through the degradation of Rhodamine B under visible light irradiation, with absorbance measurements obtained using a UV–Vis spectrophotometer at a maximum wavelength of 554 nm. The results showed that Ag doping reduced the CuO bandgap from 1.4819 eV to 1.2539 eV. Photocatalytic tests revealed that Ag-doped CuO exhibited higher activity than pure CuO, with Rhodamine B degradation reaching 60.55% at 90 minutes of irradiation, compared with only 32.72% for pure CuO at the same reaction time. This enhanced photocatalytic activity is associated with the role of Ag in suppressing electron–hole recombination, increasing light absorption through the surface plasmon effect, and providing more active sites on the catalyst surface. These findings confirm that Ag-doped CuO has promising potential as an effective photocatalyst for the treatment of textile dye wastewater and the control of environmental pollution.